Influence of frequency of feeding containing fitase on efficiency of food utilization and growth of common carp (Cyprinus carpio) fingerlings - Rachmawati, Diana; Desrina, Desrina; Wardhani, Ishana Sanjaya; Nurhayati, Dewi (Sains Akuakultur Tropis : Indonesian Journal of Tropical Aquaculture, 2024)
Local plant-based resources are widely used as ingredients in artificial feed formulations; the problem with these resources is that they contain anti-nutritional substances, namely phytate acid. An approach that can be used to overcome phytate acid is the addition of phytase to the artificial feed. The success of common carp (Cyprinus carpio) fish fingerling cultivation is supported by feed management in the form of feeding frequency that is both good and effective. The purpose of this study was to examine and find the frequency of feeding on feed utilisation and growth of common carp fingerling fed with phytase addition. This research design used an experimental method, complete randomised design (CRD), 4 treatments with 3 replications, namely treatment A (frequency of feeding once a day), treatment B (frequency of feeding twice a day), treatment C (frequency of feeding three times a day) and treatment D (frequency of feeding four times a day). The test fish used were common carp fingerling with an average weight of 1.30 ± 0.12 g/head and a stocking density of 25 fish/head size (50x50x60) cm3 which were cultured for 56 days. The variables taken include Total Feed Consumption (TFC), Efficiency of Feed Utilization (EFU), Feed Conversion Ratio (FCR), Relative Growth Rate (RGR), Survival Rate (SR), and water quality. The results showed that different feeding frequencies had a significant effect on (P<0.05) TKP, FCR, EPP, and RGR, but no significant effect on SR. The conclusion of this study was that the highest values for EPP and RGR variables were found in the frequency of feeding twice and four times a day. Keywords:  feed, phytase, growth, efficiency